EVALUASI STABILITAS DINDING PENAHAN TANAH TIPE KANTILEVER DI DESA NGROTO, KECAMATAN PUJON, KABUPATEN MALANG - Suhudi, Suhudi; Ehok, Simplisius (Prokons: Jurnal Teknik Sipil, 2021)
AbstractWavy topographical conditions with high rainfall intensity cause cantilever type retaining wall on Jalan Brigjen Abdul Manan Wijaya in Ngroto village, Pujon District, Malang Regency, which borders the Konto River avalanche. The stability of the retaining wall can be expressed as Fs (Savety Factor). Factor value the security that is reviewed is the Fs bolster, namely the safety factor against the overthrowing force, the Fs shear is the safety factor against the shear force at the base of the retaining wall, Fs, the bearing capacity of the soil is a factor safety of soil bearing capacity. The purpose of this evaluation is to determine the wall planning cantilever type retaining wall and evaluate the stability of cantilever type retaining wall against the dangers of rolling, shearing, soil bearing capacity and knowing the budget plan for wall planning Cantilever type retaining wall. The result of this evaluation shows the cantilever retaining wall with dimensions H = 7, B = 3.5 Ta = 0.5 Tb = 0.7 D = 1 declared safe with the safety value for normal water level fs slide 1.8> 1.5 (safe), fs roll 2> 1.5 (safe), fs ground bearing capacity 186.8> 4752.86 (safe). Water face flood fs shear 2,6> 1,5 (safe) fs rolling 2,3> 1,5 (safe) fs soil bearing capacity 186.8> 4752.86 (safe). The total cost required for the construction of a cantilever type retaining wall of length 20 m T = 7 width 3.5 m for Rp. 290,570,000.Keywords: Retaining walls, Dimensions, Stability of retaining walls